Peran Stakeholders Dalam Pengembangan Desa Wisata Di Desa Belumbang, Kecamatan Kerambitan, Kabupaten Tabanan, Bali - Natisha, Michelle Maria; Narottama, Nararya (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2023)
The successful development of a tourist village can be achieved through the active participation and collaboration of all related stakeholders. Each stakeholder has certain roles that should be fulfilled in the process of developing and improving the village's potential. Belumbang Village, which was inaugurated as a tourist village during the COVID-19 pandemic, faces challenges in its development. This research aims to identify the existing conditions of tourism and analyse the role of stakeholders in the development of Belumbang Tourist Village. The method used in this research is a qualitative method with data collection techniques through observation, literature review, and interviews with stakeholders who are involved in the development of Belumbang Tourist Village. The results showed that most of the stakeholders have fulfilled their roles, but it has not been done optimally. Furthermore, several issues were identified, namely the uncertainty regarding the village regulations which regulates tourism activities in Belumbang Village, limited budget for the tourism development, lack of knowledge and awareness of tourism within the local community, and also an inactive partnership between stakeholders in terms of Belumbang Tourist Village development. Keywords: tourist village, development, stakeholders, role